BERUNIYDIŃ FIZIKA HÁM ASTRONOMIYA PÁNLERI RAWAJLANIWINA QOSQAN ÚLESI - Jumamuratov, A. (SCIENCE and SOCIETY, 2023)
Our great-wise grandfather Berunius was the first in the sciences of physics and astronomy to show matter, measurement magnitudes, velocity, linear and angular velocity, weight, comparative weight, contiguous vessels, fountain, artesian wells, space, atmospheric pressure, convection, tension force between liquid particles, inertia, impact, free fall of bodies, simple mechanisms, Lunar and solar eclipses, weather, decay of particles, and other works.